Ectopic Fat Depots and Cardiometabolic Burden: A Possible Dangerous Liaison in Women Planning Assisted Reproduction - Michela Cirillo; Maria Boddi; Maria Elisabetta Coccia; Monica Attanasio; Cinzia Fatini (Tehran University of Medical Sciences, 2021)
Objective: We evaluated cardiometabolic burden in women planning assisted reproduction in order to identify subgroups at higher risk of pregnancy complications and cardiovascular disease. Materials and methods: In this cross-sectional study we investigated 60 infertile women with BMI≥25 kg/m2 referred to the Center for Assisted Reproduction. All women underwent metabolic, anthropometric parameters and ultrasound evaluation of ectopic fat depots. Results: All women had waist ≥80 cm. We found that 93.3% of women had pathological subcutaneous, 58.3% visceral and 80% para-perirenal fat; all women had fatty liver. Visceral fat and severity of steatosis were significantly related to the presence of metabolic syndrome (OR =5.7; p=0.03). A significant negative correlation between low HDL-c and para-perirenal fat (p<0.0001), a significant positive correlation with fasting plasma glucose and para-perirenal fat (p=0.001) were found. We observed a significant positive correlation between visceral fat and hs-CRP (p=0.002), HOMA-IR (p=0.04) and triglycerides (p=0.002), a significant negative correlation with HDL-c (p=0.05). Conclusion: This study by highlighting a clinically "dangerous liaison" between ectopic fat depots and metabolic/inflammatory markers, might permit to identify women with a worse metabolic phenotype and encourage lifestyle changes for improving their general and reproductive health together.